Communication between professionals from physical rehabilitation unit and deaf clients - Wiliam César Alves Machado; Juarez de Sousa Pereira; Athaynne Ramos de Aguiar Prado; Rafael André da Silva; Vera Maria da Silva; Nébia Maria Almeida de Figueiredo (Rev Rene)
Objective: to identify how professionals from the local public physical rehabilitation unit communicate with deaf peopleseeking specialized care. Methods: exploratory descriptive study with qualitative approach conducted with 32 professionalsworking in physical rehabilitation through self-reporting instrument. Results: two thematic categories emerged from dataanalysis: Using the Brazilian Sign Language, and Improvising communication strategies to interact with deaf patients. Whenprofessionals improvise strategies to communicate with the deaf, it might create barriers that negatively affect the qualityof services provided to this population. Conclusion: communication is inefficient, and effective initiatives focused on thequalification of professionals working in rehabilitation can contribute for them to master the Brazilian Sign Language,ensuring adequate care to deaf clients/patients, in the same way as those provided to people without hearing impairment.